1991
DOI: 10.1111/j.1476-5381.1991.tb12194.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phorbol ester on the release of atrial natriuretic peptide from the hypertrophied rat myocardium

Abstract: 1 To determine the cellular mechanisms of atrial natriuretic peptide (ANP) release from ventricular cardiomyocytes, the secretory and the cardiac effects of a phorbol ester, 12-0-tetradecanoyl-phorbol-13-acetate (TPA), known to stimulate protein kinase C activity in heart cells, were studied in isolated, perfused heart preparations from 2-and 21-month-old Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) rats. TPA was added to the perfusion fluid for 30 min at a concentration of 46 nm after removal of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The finding that plasma ANP was similar in WKY rats and quinapril-SHR and markedly lower than in untreated SHR supports this conclusion. Elevated ANP content in the left atrium of SHR on quinapril, in turn, probably results from reduced ANP release, since the rate of ANP synthesis in atrial tissue of SHR is known to be constant (Kinnunen et al, 1991). Thus, the results on plasma and tissue ANP concentrations confirm the normalization of blood pressure in quinapriltreated SHR.…”
Section: Discussionsupporting
confidence: 56%
“…The finding that plasma ANP was similar in WKY rats and quinapril-SHR and markedly lower than in untreated SHR supports this conclusion. Elevated ANP content in the left atrium of SHR on quinapril, in turn, probably results from reduced ANP release, since the rate of ANP synthesis in atrial tissue of SHR is known to be constant (Kinnunen et al, 1991). Thus, the results on plasma and tissue ANP concentrations confirm the normalization of blood pressure in quinapriltreated SHR.…”
Section: Discussionsupporting
confidence: 56%
“…However, ANP mRNA expression in LV was equal in young SHR and WKY. At 21 months of age, ventricle weight of SHR had increased further to about 170%, and ANP mRNA reached 3.7-fold values compared to age-matched WKY ( Kinnunen et al, 1991 ). We found a similar relation of HW/BW between our young SHR and WKY.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning ANP mRNA expression, we also found that activation of PKC resulted in the induction of myocardial ANP mRNA with a transient maximum at 60 minutes in lean Zucker rats. Because it has been shown that in the adult heart ventricles PMA had no effect on ANP secretion, 37,38 it can be speculated that the transient increase in ANP mRNA observed in heart ventricles from adult lean Zucker rats results from a possible negative feedback mechanism resulting from ANP accumulation. With a finding similar to our own, Cornelius et al 39 reported a transient increase in ANP mRNA 120 minutes after imposition of elevated wall stress and 90 minutes after forskolin stimulation.…”
Section: Discussionmentioning
confidence: 99%